2017
DOI: 10.15171/ijep.2017.06
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Grouping and Phenotypic Detection of Extended-Spectrum β-Lactamases Among Escherichia coli From Calves and Dairy Cows in Khuzestan, Iran

Abstract: Background: Food-producing animals are under suspicion for the reservoir and colonization of ESBL (extended-spectrum beta-lactamase)-producing bacteria especially Enterobacteriaceae and therefore infection of the humans with them. The increasing reports on the ESBLs presence in the pathogenic and commensal Escherichia coli isolates have been a concern worldwide. These strains can be attributed to one of the main phylogenetic groups and subgroups. Several studies have shown the relationship between the phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
4
6
1
Order By: Relevance
“…and D2. Pathogenic intestinal E. coli (DEC) mainly belong to Phylogenetic groups A, B1, and D, commensals to the groups A and B1, and strains usually belong to the groups B2 and D [13,14]. In our study, phylogenetic analysis predominantly clustered E. coli clinical isolates into B2 followed by A, B1 and D and this corroborates with ndings from previous studies [67][68][69].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…and D2. Pathogenic intestinal E. coli (DEC) mainly belong to Phylogenetic groups A, B1, and D, commensals to the groups A and B1, and strains usually belong to the groups B2 and D [13,14]. In our study, phylogenetic analysis predominantly clustered E. coli clinical isolates into B2 followed by A, B1 and D and this corroborates with ndings from previous studies [67][68][69].…”
Section: Discussionsupporting
confidence: 92%
“…Ampli cation was conducted using the following PCR conditions; initial denaturation at 94 °C for 5 minutes, then 30 cycles performed at 94 °C for 5 seconds, 54 °C for 10 seconds, 72 °C for 30 second with a nal extension step at 72 °C for 5 minutes. Phylogenic groups and subgroups were assigned depending on chuA, yjaA, and TspE4.C2 gene combinations [13,14], Table 5. CGC GCC AAC AAA GTA TTA CG and L-ETEC (2.0%).…”
Section: Pai Iicft073mentioning
confidence: 99%
“…Phylogenetic analysis revealed that E. coli isolates obtained from the four tertiary hospitals located in the Central region (MNRH), Western region (MBRRH), South Western Region (KIU-TH) and Eastern Region (MRRH) belonged to the phylogroups A B1, B2 and D and phylogenetic sub groups A0, A1, B22, B23, D1 and D2. Pathogenic intestinal E. coli (DEC) mainly belong to Phylogenetic groups A, B1, and D, commensals to the groups A and B1, and strains usually belong to the groups B2 and D [13,14]. In our study, phylogenetic analysis predominantly clustered E. coli clinical isolates into B2 followed by A, B1 and D and this corroborates with ndings from previous studies [67][68][69].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, PCR analysis clusters E. coli strains into A, B1, B2, and D phylogenetic groups due to the presence of the chuA and yjaA genes as well as TSPE4.C2 DNA fragment [13]. The intestinal pathogenic E. coli strains belong to groups A, B1 and D, extraintestinal pathogenic E. coli strains generally follow under groups B2 and D, while commensal E. coli strains to groups A and B1 [13,14] High levels antibiotic resistance in Enterobacteriaceae is of great concern to the healthcare system [15,16]. Escherichia coli like other Enterobacteriaceae has evolved to acquire different mechanisms of antibiotic resistance which confer protection to lethal doses of different classes of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The second continent with the highest number of countries reporting E-ESBL in cattle is Asia, which shows description of E-ESBL in 13 countries (China, Hong Kong, India, Indonesia, Iran, Israel, Japan, Lebanon, Malaysia, Saudi Arabia, South Korea, Thailand and Taiwan), highlighting China and India which are the fourth and fifth largest cattle producers in the world (Adler et al, 2015;Ali et al, 2017;Barzan et al, 2017;Diab et al, 2016;Hassan et al, 2015;Hinthong et al, 2017;Kamaruzzaman, 2015;Koovapra et al, 2016;Ohnishi et al, 2013a;Su et al, 2016;Sudarwanto et al, 2016;Tark et al, 2017). They have different roles in the import and export scenario, as India is the world's largest exporter of cattle and China the largest importer, since its internal production is not sufficient for internal consumption (USDA et al, 2017).…”
Section: Asiamentioning
confidence: 99%